Student Support System in the Next Normal Era: A Case Study of a School Under the Office of Special Education Administration in the Southern Border Provinces - Saiuseng, Tuwaerponarama; Maitreephun, Warapark (Journal of Information and Learning [JIL], 2024)
The objectives of this research were to study 1) the problems encountered by students, 2) the operating processes of the student support system, and 3) the recommendations from stakeholders for operating the student support system in the next normal era. This study examined the case of one school under the Office of Special Education Administration in the southern border provinces. This study used a semi-structured interview protocol, observation form, and document analysis as research instruments. The interviews were conducted with 11 stakeholders. The collected data were analyzed using content analysis. The data triangulation technique was used to promote trustworthiness. The results showed that the problems faced by students include physical dimensions, technological readiness, teaching and learning, student mental health, and family and social relations. The study also found that the operating process of the student support system includes getting to know individual students by interviewing students and parents and visiting their homes to record an online database system, screening student cases by resident teachers using the Strengths and Difficulties Questionnaire (SDQ), preventing and solving the problem by adding an investigating room, promoting positive disciplines, deducting a behavioral score, organizing relevant activities, and conducting moral and ethical training, promoting student development by providing opportunities for students to demonstrate their abilities, participate in academic skills competition, and receive vocational skills training, and referring the cases to school Islamic teachers or external agencies, such as other appropriate schools or drug dependence treatment hospitals. Furthermore, the recommendations from stakeholders to support students in the next normal era include intensifying the screening of students, using information technology to create a student database, and supporting every school to have a psychologist.